2021
DOI: 10.1097/ju.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stent Placement following Ureteroscopy Increases Emergency Department Visits in a Statewide Surgical Collaborative

Abstract: Introduction: Ureteral stents are commonly placed after ureteroscopy (URS). Though studies indicate that stents are associated with patient discomfort, their impact on downstream health services use is unclear. We examined patterns of stent utilization in Michigan and their association with unplanned healthcare encounters.Methods: We used the Michigan Urologic Surgery Improvement Collaborative's Reducing Operative Complications from Kidney Stones (MUSIC ROCKS) clinical registry to identify URS cases between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Several studies have shown comparable outcomes between unstented and stented groups in terms of early postoperative problems, including low-grade fever, hematuria, urinary tract infection, and flank pain [ 13 , 16 ]. A recent paper reported that stent placement during URS was independently associated with a 25% increase in emergency room visits within 30 days, with flank pain being the most common reason for both groups, but there was no increased risk of hospitalization [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown comparable outcomes between unstented and stented groups in terms of early postoperative problems, including low-grade fever, hematuria, urinary tract infection, and flank pain [ 13 , 16 ]. A recent paper reported that stent placement during URS was independently associated with a 25% increase in emergency room visits within 30 days, with flank pain being the most common reason for both groups, but there was no increased risk of hospitalization [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details on the ROCKS (Reducing Operative Complications from Kidney Stones) initiative and clinical registry have been previously described. 4,17,18 Each MUSIC practice has obtained an exemption or approval by the local Institutional Review Board for participation in the collaborative. This study was conducted by the MUSIC coordinating center and, thus, participants were limited to those within the state of Michigan.…”
Section: Musicmentioning
confidence: 99%
“…1,2 However, stenting remains a common practice, occurring in over two-thirds URS for urinary stone disease. 3,4 Stents are associated with pain and urinary symptoms, 5 as well as increased risk of an emergency department visit after URS. 4,6,7 These unplanned encounters substantially increase the cost of URS.…”
mentioning
confidence: 99%
“…These findings are consistent with reports of thermal injury and stricture after ureteroscopy with TFL in the ureter [8] . In clinical practice, 60–70% of upper urinary tract stones treated with ureteroscopy are located in the ureter [9] . For this location, holmium laser offers predictability and safety.…”
mentioning
confidence: 99%